Factors associated with relapses among patients treated for acute urticaria. Issue 5 (28th February 2019) - Maillet, Florent; Wolff, Dorian; Soria, Angele; Adnet, Frederic; Panayotopoulos, Virginie; Gobert, Delphine; Lapostolle, Frederic; Reuter, Paul‐Georges; Ghazali, Aiham; Caux, Frederic; Fain, Olivier; Javaud, Nicolas
Abstract: The benefit of corticosteroids in acute urticaria is controversial. Our objective was to determine the factors associated with relapses in patients presenting with acute urticaria. A retrospective observational study, including all patients with acute urticaria who visited the angioedema reference center of Academic Public Hospitals – Saint‐Antoine in Paris between January 2015 and June 2017, was conducted. The study inclusion criterion was a diagnosis of acute urticaria in an adult patient. The urticaria was spontaneous or inducible urticaria. The primary outcome was relapse at day 7 and the secondary outcome was relapse at week 6. A total of 184 patients with a first episode of acute urticaria were included. Most of the patients were female (66%) with a mean age of 42 ± 16 years. Corticosteroid administration for treatment of acute urticaria was used in 102 (55%) patients. Overall, 85 (46%) patients had relapses after less than 7 days whereas 168 (91%) patients had relapses after more than 6 weeks. In univariate analysis, the rate of corticosteroid administration was significantly higher in cases of relapse after less than 7 days. No difference in relapse rates after more than 6 weeks appeared. In the multivariate analysis, the independent factor associated with relapses after less than 7 days was the administration of corticosteroids as treatment of acute urticaria (odds ratio, 1.93; 95% confidence interval, 1.06–3.57; P = 0.03). The prevalence of corticosteroid administration for patients with acute urticaria was high. Corticosteroid administration was an independent risk factor associated with relapses after less than 7 days.